2021
DOI: 10.3389/fgene.2021.637322
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Single-Cell RNA-seq Data to Uncover the Association Between Cell Type and Chronic Liver Diseases

Abstract: BackgroundComponents of liver microenvironment is complex, which makes it difficult to clarify pathogenesis of chronic liver diseases (CLD). Genome-wide association studies (GWASs) have greatly revealed the role of host genetic background in CLD pathogenesis and prognosis, while single-cell RNA sequencing (scRNA-seq) enables interrogation of the cellular diversity and function of liver tissue at unprecedented resolution. Here, we made integrative analysis on the GWAS and scRNA-seq data of CLD to uncover CLD-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…scRNA-seq can provide a comprehensive understanding of the pathogenesis of HCC and is conducive to individualized treatment of HCC. Multiple studies analyzed the scRNA-seq data from healthy controls, tumor tissues and adjacent tissues, and the results showed that the difference of proportion of various immune cells, including CD8 + T cells, NK cells, macrophages, B cells and other cells (58)(59)(60)(61). The changes of infiltrated immune cells may be related to the immunosuppressive microenvironment in HCC and correlated with HCC progression (62).…”
Section: Discussionmentioning
confidence: 99%
“…scRNA-seq can provide a comprehensive understanding of the pathogenesis of HCC and is conducive to individualized treatment of HCC. Multiple studies analyzed the scRNA-seq data from healthy controls, tumor tissues and adjacent tissues, and the results showed that the difference of proportion of various immune cells, including CD8 + T cells, NK cells, macrophages, B cells and other cells (58)(59)(60)(61). The changes of infiltrated immune cells may be related to the immunosuppressive microenvironment in HCC and correlated with HCC progression (62).…”
Section: Discussionmentioning
confidence: 99%
“… 58 100 101 102 103 In the future, a unique application of scRNA-seq in combination with such GWAS analyses could delineate the precise cellular source of such disease-associated gene variants. 104 105 While these combined analyses are still being refined, they have previously clarified the cellular origins for genetic alterations of interest in ulcerative colitis 105 and could be applied to autoimmune liver diseases.…”
Section: Future Perspectivesmentioning
confidence: 99%